On the Distribution of Income and Worker Assignment under Intrafirm Spillovers, with an Application to Ideas and Networks - Saint‐Paul, Gilles (Journal of Political Economy, 2001)
I study the earnings structure and the equilibrium assignment of workers when workers exert intrafirm spillovers on each other. I allow for arbitrary spillovers provided that output depends on some aggregate index of workers’ skill. Despite the possibility of increasing returns to skills, equilibrium typically exists. I show that equilibrium will typically be segregated and that the skill space can be partitioned into a set of segments and any firm hires from only one segment. Next, I apply the model to analyze the effect of information technology on segmentation and the distribution of income. There are two types of human capital, productivity and creativity, that is, the ability to produce ideas that may be duplicated over a network. Under plausible assumptions, inequality rises and then falls when network size increases, and the poorest workers cannot lose. I also analyze the impact of an improvement in worker quality and of an increased international mobility of ideas.